Inovasi Pelayanan Publik â€œSapaku Malamâ€ di Kecamatan Kuta Utara, Kabupaten Badung - Ida Ayu Ratna Kartika Dewi (Public Inspiration : Jurnal Administrasi Publik, 2020)
Until now, public services in Indonesia in general are still many problems. The need for ideal services has not yet materialized. One of the most important processes in realizing public service improvement is to make an innovation breakthrough. The existence of laws and regulations governing regional innovation becomes a reference for the Regional Government to innovate in order to improve the quality of public services. One of them is the public service innovation â€œSapaku Malamâ€ in Kuta Utara District, Badung Regency. This type of research is qualitative descriptive with data collection techniques through observation, interviews and documentation. This study aims to determine the implementation, driving and inhibiting factors, and the impact of the public service innovation. The results showed that the implementation of the Public Service Innovation "Sapaku Malam" in North Kuta District, Badung Regency in general has been going well. The driving factors for innovation are the pro-innovation organizational structure and culture; and competent human resources who have a high commitment to improve service quality. The inhibiting factor for innovation are the absence of a special budget planning for innovation; and disruption of internet systems and networks. The innovation has a significant impact on society in terms of cost and time efficiency. For the North Kuta District Government, innovation has an impact on improving the quality of public services so as to realize effective and efficient public services.